2018
DOI: 10.1186/s11689-018-9240-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and maternal predictors of cognitive and behavioral trajectories in females with fragile X syndrome

Abstract: BackgroundFragile X syndrome (FXS) is caused by a mutation in the FMR1 gene on the X chromosome, leading to decreased levels of FMR1 protein (FMRP), which causes the array of neuropsychological impairments that define FXS. Because FXS is an X-linked condition, fewer females display FXS and females with FXS are more mildly affected than males, on average. However, there is a considerable variability in terms of severity of affectedness among females with FXS. The current study was designed to investigate potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…The variation in phenotype among females with full mutation FXS can, at least in part, be attributed to a phenomenon known as X inactivation [11,13]. X inactivation is thought to occur so that females have approximately equal X chromosome gene dosage despite having twice as many X chromosomes (known as “dosage compensation” [14]).…”
Section: Geneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variation in phenotype among females with full mutation FXS can, at least in part, be attributed to a phenomenon known as X inactivation [11,13]. X inactivation is thought to occur so that females have approximately equal X chromosome gene dosage despite having twice as many X chromosomes (known as “dosage compensation” [14]).…”
Section: Geneticsmentioning
confidence: 99%
“…It is likely that these declines are not due to the loss of skills, but rather to a slowing rate of acquisition of new skills compared to typically developing peers, as well as the increasingly strenuous cognitive demands placed on children as they age. A recent longitudinal study on girls with FXS suggested that, while fluid intelligence was predicted only by biological or genetic factors, crystalized intelligence may be related to maternal mental health and perceived closeness of mother–child relationship [13]. Taken together, these studies suggest a vulnerable time frame in which girls with FXS are prone to decline in cognitive scores, and the importance of protective factors, such as an enriched environment, that may help mitigate this decline.…”
Section: The Fragile X Phenotype In Femalesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the language environment in which an individual develops can have strong influences on language development [70,71]. In addition, higher levels of parental education are associated with better expressive language skills in TD children [72,73], as well as in individuals with ID [6,[74][75][76][77]. Studies focused on individuals with FXS or DS have also suggested a positive association of maternal education with expressive vocabulary outcomes after controlling for CA [78].…”
Section: Sources Of Variation In Expressive Language Development In Imentioning
confidence: 99%
“…Maternal mental health has also been found to be associated with expressive language development in TD children [86] and in individuals with ID [75][76][77]. Depression, for example, can impede a person's ability to respond optimally in interactions with their children, which, in turn, can impede language development [87].…”
Section: Sources Of Variation In Expressive Language Development In Imentioning
confidence: 99%